One hundred years of Surrealist poetry theory and practice - Bohn, Willard 1939- (New York Bloomsbury Academic, 2023)
Tells the story of the origins and growth of Surrealist literature - primarily through poetry written in French, Spanish, Catalan, and Portuguese - throughout the western hemisphere, examining its popularity, influence, and variety"-- Provided by publisher.
Includes bibliographical references and index.
Keywords: Surrealism (Literature).; Romance-language poetry -- History and criticism